Nutritional value and coagulation properties of milk from local cow breeds, including the selected macro- and micronutrients and trace elements - Anna Teter; Monika Kędzierska-Matysek; Joanna Barłowska; Jolanta Król; Aneta Brodziak (Mljekarstvo)
The aim of the study was to assess the nutritional value of milk based on its chemical composition and content of selected minerals and to determine the coagulation properties of raw milk from native Polish breeds, i.e. the Polish Red and the White-backed, as well as locally raised Simmental cows, taking into account the production season. The research material consisted of 418 milk samples taken during the spring/summer season (April to September) and autumn/winter season (October to March). The following parameters were determined in the samples: chemical composition, energetic value, coagulation properties (RCT - rennet clotting time, A30 - curd firmness, K20 - curd firming time), cheese yield, and content of K, Na, Ca, Mg, Zn, Fe, Mn, Cu, Ni and Co. The percentage of the daily allowance for Ca and Mg in children, adolescents and adults from 250 mL of milk was determined. The milk of Polish Red cows had the highest concentration of basic nutrients (1 kg of milk provided 823.98 kcal) and the best coagulation parameters (the shortest clotting time (16:09 min, p≤0.01) and firmest curd (30.74 mm). This milk had a more beneficial nutritional profile, as it contained the highest percentage of the recommended daily allowances of Ca and Mg among all groups. The raw milk obtained in the pasture season showed more favourable coagulation properties. The content of minerals in milk is not clearly determined by the cow breed or the season. It is probably due to the higher levels of these nutrients in the feed, which in turn results from their content in the soil and the degree of fertilization.